The nature of axonal arborization occurring under the action of low-frequency electromagnetic fields. - Pivovarenko, Y. V. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. Previously, it was found that the drying of salt solutions prepared on water with a negative charge is accompanied by the arborization of salt crystals, i.e. – the formation of needle- or plant-shaped crystals. It was also found that low-frequency electromagnetic fields stimulate the regeneration of damaged neurons. Objective. The aim of the work was to test the hypothesis that negative electrization of the cytoplasm of neurons, as well as their axonal arborization, can occur under the influence of low-frequency electromagnetic fields. Methods. For the negative electrization of aqueous solutions of chlorides, various low-frequency (0 ÷ 100 Hz) EMF generators were used. Negative electrization of aqueous solutions of chlorides was visualized using the method of sensitive crystallization. Results. It is shown that under the action of low-frequency electromagnetic fields, arborization of chlorides, which are the main salt components of the cytoplasm of cells, including neurons, occurs. This made it possible to explain the nature of axonal arborization of damaged neurons, which is observed under the influence of low-frequency electromagnetic fields in vivo. Conclusion. Under the action of low-frequency electromagnetic fields, negative electrization of aqueous solutions of chlorides occurs. By preliminarily optimizing the content of chlorides in the body, it is possible to create optimal conditions for the axonal arborization of neurons and the formation of new capillaries using low-frequency electromagnetic fields.